RANCANGAN INOVASI LOCAL TRANSLATOR: SOLUSI TEKNOLOGI UNTUK MENINGKATKAN KOMUNIKASI DAN PELESTARIAN BAHASA DAERAH DI INDONESIA - Birgita Herna Angelita; Kevin R. Silalahi; Anike Dzun N. A. A; Endang Purwasari (Institut Seni Indonesia Surakarta, 2024)
The problem of communication gaps due to language differences is often encountered, especially by students leaving their hometowns to go to a foreign region. Indonesia has more than 700 regional languages; this diversity sometimes causes communication failures. The ISI Surakarta Community ServiceTeam initiated a digital application design to make communication easier. Local Translator is an innovative technology application designed to bridge language differences in Indonesia. This activity uses a participatory action research (PAR) approach. This service model is designed to provide a broader impact by involving participants in the application development process. The ultimate goal of this service activity is to become a bridge for cross-cultural communication and facilitate the preservation of regional languages.